Execução provisória em processo penal condenatório confrontada com o princípio constitucional de presunção de inocência - Maia, Caio Matheus Ferreira (Universidade Federal Rural do Semi-Árido, 2018)
This research aims to promote an analysis based on provisional execution of custodial penalty, started from the confirmation of the sentence by the appeal court, beneath the perspective of the principle of presumption of innocence, confronted with the decision whom allowed the execution. The Federal Constitution explicitly says in its list of fundamental rights and guarantees that no one shall be considered guilty before the final and unappealable criminal sentence, in other words, when exhausted the possibilities of appeal and the decisum become immutable. However, what occurs is that the Supreme Court recently decided by the possibility of starting the execution of custodial penalty when the condemnatory decision is still pending special or extraordinary appeal, that is to say, before the final and unappealable decision. The decision brought a tough discussion between legal practitioners and the own ministers of the highest level in judiciary power, since for some the decision goes against with the text expressed in the National Constitution, mitigating a provided constitutional guarantee. Thus, it analyzes the institute of provisional execution of the sentence with the main focus on the doctrinal debate about the mitigation or not of the principle of presumption of innocence, eternity clause of legal order. The qualitative and explicative method of research was used, which turned possible studying about the theme by means of the doctrine and the current jurisprudence.
Artigo Acadêmico
Keywords: Execução provisória; Pena privativa de liberdade; Princípio da presunção de inocência; Direitos e garantias fundamentais; Provisional execution; Principle of presumption of innocence; Custodial penalty; Rights and fundamental guarantees; CIENCIAS SOCIAIS APLICADAS::DIREITO